A Reply to Professor Tobias - Peter A. Appel (Washington University Law Quarterly, 2000)
Professor Tobias finds four primary faults with my account. First, he believes that I rely too heavily on impressionistic and anecdotal data in formulating my conclusions, although he recognizes that all analyses of intervention— his own included— suffer from the same fault. Second, he argues that my article and other considerations of this area would benefit from “a more refined understanding of modern environmental litigation.” Third, Professor Tobias expresses doubt about the wisdom of my prescriptions for improving intervention, particularly with my argument that courts of appeals should review intervention denials under an abuse of discretion standard rather than de novo. Fourth, and finally, he argues that my article “clings too substantially to a private law view of environmental litigation and participation in it.” I will deal with each of these criticisms in turn.
Keywords: Citizen suits (Civil procedure); Intervention (Civil procedure); Environmental law; Public law